Decolonising and demedicalising intersex research. (May 2022) - Roen, Katrina; Oliver, Eli
In this commentary, we examine the role of non-Indigenous psychology researchers in settler states such as Aotearoa / New Zealand. A key focus is on demedicalising and decolonising intersex. We describe approaches to knowledge production that are based on the decolonising thinking of Indigenous and non-Indigenous researchers, and that open up opportunities for resistance and transformation. We then examine how decolonisation can be brought into dialogue with demedicalisation. Finally, we consider opportunities for an Indigenous understanding of health to contribute to the demedicalising aspirations of intersex advocates and researchers.